Advances in the experimental and theoretical understandings of antibiotic conjugated gold nanoparticles for antibacterial applications - Khandelwal, Puneet; Singh, Dheeraj K.; Poddar, Pankaj (ChemistrySelect, 2019)
The worldwide bacterial resistance to a wide range of antibiotics originates a global health concern and calls for the development of new antibacterial agents. Over the recent years, nanomaterials-based agents have been proven to be useful for the effective antibacterial applications. Notably, the gold nanoparticles (AuNPs) draw particular attention due to their biological inertness and easy surface functionalization. It is now established that the antibiotic functionalization on the AuNPs surfaces increases the antibacterial efficacy even towards the antibiotic-resistant bacterial cells. Moreover, the antibacterial efficacy can be further enhanced by photothermal therapy using antibiotic conjugated AuNPs. In this review article, we have reviewed the advances in the development of the synthesis methods of antibiotic conjugated AuNPs and gold nanoclusters, and their antibacterial efficacy. We have also discussed the developments in the theoretical understandings behind the interaction of antibiotic molecules with gold surface and its relation to the antibacterial activity. We believe that few parameters including the selection of antibiotic molecules, the method of its attachment to AuNPs, the purification of antibiotic conjugated AuNPs, and the quantification of conjugated antibiotic are crucial and needs to be properly addressed. Moreover, there are many other future directions discussed, for using antibiotic conjugated AuNPs more effectively for antibacterial therapy.
Keywords: Antibacterial; antibiotic; DFT calculations; gold nanocluster; Gold nanoparticle; multi-drug resistance; photo-thermal therapy